Relationship between Husband's Support, Knowledge Level, and Motivation with IVA Examination Behavior in Women of Childbearing ge in Padang City - Intan Firmana Putri; Ferdinal Ferry; Hafni Bachtiar (Universitas Andalas, 2021)
Background: Cancer is the second leading cause of death in the world. Cervical cancer is in the 9th position out of 35 types of cancer causing the most deaths in the world. Cervical cancer is the second highest type of cancer after breast cancer in women, which affects more than 1.4 million women worldwide. Every year more than 460,000 cervical cancer incidents occur and about 231,000 women die from the disease.Objectives: This study aims to determine the relationship between husband's support, level of knowledge and motivation, with the behavior of IVA examination in fertile aged women in the city of Padang.Methods: This research is an analytic observational study with cross-sectional comparative study approach that looks at the relationship between knowledge, motivation, and husband's support with IVA examination behavior in women of childbearing age.Results: The percentage who did not perform IVA examination was higher among respondents with low motivation compared to those with high motivation, namely 54.7% versus 45%. Statistically this difference was not significant (p> 0.05). The number of respondents who did not perform IVA examinations was higher for respondents with less husband's support, namely 32 respondents (42.1%) and more than half of respondents who did IVA examinations, namely 44 respondents (57.9%) who received less support from their husbands. Statistically this difference was significant (p <0.05).Conclusion: There is a relationship between the level of knowledge and the behavior of the IVA examination, there is no relationship between motivation and the behavior of the IVA examination and there is a relationship between the level of knowledge and the behavior of the IVA examination.Keywords: IVA, women of childbearing age, education